Synthesis of acrylonitrile functionalized hydroxymethylfurfural derivatives with Mg(OH)2 under solvent-free conditions - Mancipe, Sonia (2023)
Hydroxymethylfurfural (HMF) derivatives that contain an acrylonitrile group result in inter-esting scaffold molecules that can be obtained from biomass. However, the synthesis of these typesof molecules has not been extensively studied. In this study, we investigated the catalytic activity ofMg(OH)2 and MgO materials. Specifically, we evaluated the Knoevenagel reaction between HMF andmalononitrile as a test reaction under solvent-free conditions. The fresh and used catalysts were eval-uated using various techniques. Our results indicate that the combination of synthesis methods in-fluences the crystalline, basic, and textural properties of the catalysts. We found that water plays anessential role in obtaining high yields. By using this simple and inexpensive method, we were able toachieve yields near 90% in short reaction times (<30 min).Keywords. HMF, Active methylene, Brucite, Solvent-free, Knoevenagel reaction.